Answer:
The equation of the tangent line
[tex]y - \frac{\pi }{4} = (\frac{-\pi }{2} +1)( x - \frac{\pi }{4} )[/tex]
Step-by-step explanation:
Step(i):-
Given function y = x cot (x) ....(i)
Differentiating equation (i) with respective to 'x' , we get
[tex]\frac{dy}{dx} = x (-Co sec^{2} (x)) +cot(x) (1)[/tex]
Step(ii):-
The slope of the tangent line
[tex]\frac{d y}{d x} = -x Co-sec^{2} (x) +cot x[/tex]
[tex](\frac{d y}{d x} )x_{=\frac{\pi }{4} } = -\frac{\pi }{4} Co-sec^{2} (\frac{\pi }{4} ) +cot \frac{\pi }{4}[/tex]
We will use trigonometry formulas
[tex]Cosec(\frac{\pi }{4} ) = \sqrt{2}[/tex]
[tex]sec(\frac{\pi }{4} ) = \sqrt{2}[/tex]
[tex]Cot(\frac{\pi }{4} ) = 1[/tex]
Now the slope of the tangent
[tex]\frac{dy}{dx} =-\frac{\pi }{4} (\sqrt{2})^{2} )+1[/tex]
[tex]\frac{dy}{dx} =-\frac{\pi }{2} +1[/tex]
Step(iii):-
Given
Substitute [tex]x=\frac{\pi }{4}[/tex] in y = x cot (x)
[tex]y = \frac{\pi }{4} cot (\frac{\pi }{4} )[/tex]
[tex]y = \frac{\pi }{4}[/tex]
The point of the tangent line [tex](x ,y ) = (\frac{\pi }{4} , \frac{\pi }{4} )[/tex]
The equation of the tangent line
[tex]y - y_{1} = m ( x - x_{1} )[/tex]
[tex]y - \frac{\pi }{4} = (\frac{-\pi }{2} +1)( x - \frac{\pi }{4} )[/tex]